Modern Tailoring in Linear Rebellion Fashion Collection at Danjyo Hiyoji - Fadillah Riffalia; Marthatiar Withney Elvyara; Adhi Kusumastuti; Michaela Rouli Margareta Siahaan (Journal of Creativity Student, 2026)
The fashion industry continues to develop along with the increasing demand for products that possess not only aesthetic value but also a strong visual identity. Danjyo Hiyoji is one of Indonesia’s local fashion brands recognized for its contemporary streetwear concept combined with modern tailoring. This article aims to describe the development process of the Linear Rebellion fashion collection through the application of modern tailoring and decorative details as a final project during the Industrial Practice Program at Danjyo Hiyoji. The study employed a descriptive quantitative method with a design development approach supported by observation, documentation, literature review, and product assessment by panelists. The development stages included visual research, moodboard preparation, concept development, design creation, material selection, production process, and final product evaluation. The Linear Rebellion concept was represented through vertical stripe motifs symbolizing order and exposed zipper details symbolizing courage in exploring fashion design. The evaluation results indicated that the collection achieved an average score of 95.93%, categorized as excellent. The design aspect obtained 96.66%, size 98.90%, aesthetics 85.56%, sewing technique 100%, garment performance 98.90%, and uniqueness 95.56%. These findings demonstrate that the application of modern tailoring and decorative details successfully produced a fashion collection with excellent construction quality, functionality, aesthetics, and a strong visual identity in accordance with the design characteristics of Danjyo Hiyoji.